Production of Sustainable Proteins Through the Conversion of Insects to Proteins Using Beauveria bassiana Cultures - Gutiérrez Román, Ana I. F.; Laynes Zela, Pedro F.; Acuña Payano, Rosalyn K.; Nolasco Cárdenas, Oscar P.; Santa-Cruz Carpio, Carlos M.; Leiva Eriksson, Nélida R. (Frontiers in Sustainable Food Systems, 2022)
Various strategies are being suggested to solve the challenges in the food system, such as changing the source of nutrients, including the use of non-traditional food sources such as insects. Although insects are promoted as a cheap and sustainable source of protein, consumers are reluctant to eat them. The mycoproteins produced by fungi, on the other hand, are very well received and appreciated by consumers. Thus, in this work we have studied the use of the entomopathogenic fungi Beauveria bassiana (Ascomycota: Hypocreales) for the production of protein using insects as feed. B. bassiana was cultivated in culture medium containing entire insects from the species Eurysacca and Hypothenemus or single carbon sources such as glucose or laminarin from Laminaria digitata. The results showed that B. bassiana can produce up to 16-fold more biomass and 8-fold more protein when grown in insect-based medium than when grown in glucose. The results also indicated that the production of proteins continuously increased when B. bassiana was grown in medium containing insects, reaching its maximum at 9 days (up to 3 mg/mL). On the other hand, when cultivated in glucose-supplemented medium, the production of proteins was constantly low (~0.5 mg/mL). In conclusion, B. bassiana was a large biomass producer and exuded a large amount of protein when grown in medium containing insect powder, making it an ideal intermediate link between insects and protein. Furthermore, the proteins produced by fungi such as B. bassiana can be used in the food, health, and cosmetic industries.